Antarctic Salt-Cones: An Oasis of Microbial Life? The Example of Boulder Clay Glacier (Northern Victoria Land) - Maurizio Azzaro; Maria Papale; Carmen Rizzo; Emanuele Forte; Davide Lenaz; Mauro Guglielmin; Angelina Lo Giudice (Microorganisms, 2022)
The evaporation of a localized, highly saline water body of the Boulder Clay debris-covered glacier, in the Northern Victoria Land, probably generated the accumulation of mirabilite (Na2SO4 × 10H2O) and thenardite (Na2SO4) in a glacier salt-cone. Such an extremely cold and salty environment resembles the conditions on Mars, so it can be considered a terrestrial analog. The study was aimed at gaining a first glimpse at the prokaryotic community associated with Antarctic mirabilite and thenardite minerals and also to find clues about the origin of the salts. For this purpose, samples were analyzed by a next generation approach to investigate the prokaryotic (Bacteria and Archaea) diversity. Phylogenetic analysis allowed the identification of Bacteroidota, Actinobacteriota, Firmicutes, and Gammaproteobacteria as the main bacterial lineages, in addition to Archaea in the phylum Halobacterota. The genera Arthrobacter, Rhodoglobus, Gillisia, Marinobacter and Psychrobacter were particularly abundant. Interestingly, several bacterial and archaeal sequences were related to halotolerant and halophilic genera, previously reported in a variety of marine environments and saline habitats, also in Antarctica. The analyzed salt community also included members that are believed to play a major role in the sulfur cycle.